Role of High Dose Calcium in the Prevention of Preeclampsia (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Objectives: To assess the effect of supplementation of high dose of calcium(2gm) in prevention of preeclampsia.Materials & Methods: A randomized controlled clinical trial on 272 healthy nulliparous woman were randomly allocated into two groups by means of a computer generation randomization list. From 20 weeks of gestation until delivery who received 2gm of oral elemental calcium per day (n=127 )were assigned to high dose calcium group or the study group and 145 women were assigned to low dose calcium or control group , receiving 500 mg of calcium per day. Ten women (3.67%) were lost to follow up after randomization (4 in the study group and 6 in the control group) . Thus a total of 123 woman in the study group and 139 in the control group were included in the final analysis. Data was collected by standard questionnaire, clinical examination and investigations and statistical analysis was performed by students t-test, chi square tests. P